'I don't get time only': an apparent-time investigation of clause-final focus particles in Asian Englishes. Issue 3 (2nd September 2019) - Parviainen, Hanna; Fuchs, Robert
ABSTRACT: Research on the historical development of varieties of English usually tracks influence from established, so-called Inner Circle, varieties of English (such as British English) to less established Outer Circle varieties (such as Indian English). Recently, evidence of convergent patterns of language use in a number of Outer Circle Asian varieties has emerged, which might have been caused by the influence of Indian English in the region, but the existing evidence is strictly synchronic. Using the apparent-time method, this article investigates the focus particles 'also' and 'only', which have developed new uses in Asian Englishes. We provide evidence of language change in progress in Indian English and Hong Kong English, suggesting that Indian English might have influenced Hong Kong English, while evidence of Indian English influencing Philippine English remains tentative. The results lend support to a description of Indian English as a 'super-central variety' that has some influence over other varieties, thus challenging the traditional account of the development of varieties of English.